Levels of serum trace elements in patients with Peyronie. (2nd July 2020) - Gunes, Mustafa; Aslan, Rahmi; Eryılmaz, Recep; Demir, Halit; Taken, Kerem
Abstract: Aim: The etiology of the disease of Peyronie is not certainly known. However, penile micro traumas are thought to be important in the pathogenesis of Peyronie's disease (PD) in genetically predisposed individuals. In this study, we aimed to determine the relationship of some trace element and heavy metals with PD. Material and methods: Thirty Peyronie patients and 26 healthy volunteers were included in the study. In individuals in both groups, levels of serum trace elements (Manganese [Mn], Cu, Cobalt (Co), zinc [Zn], Cd, and iron [Fe]) were determined separately by Atomic Absorption Spectrophotometer method in Yüzüncü Yıl University Central Research Laboratory. Results: Mn, Cu, Zn, and Fe levels in Peyronie patients were statistically significantly lower when compared to the healthy control group ( p  < .05). Cd and Co levels were similar for both groups but not statistically significant ( p  > .05). Conclusions: The changes in trace element levels are related to the etiopathogenesis of PD. We think that our study is the first from this aspect.